2021
DOI: 10.3390/ijerph182111524
|View full text |Cite
|
Sign up to set email alerts
|

Educational Aspirations and Expectations of Adolescents in Rural China: Determinants, Mental Health, and Academic Outcomes

Abstract: Educational aspirations and expectations of adolescents have implications for educational and psychological outcomes. This study aimed to determine factors associated with educational aspiration–expectation discrepancies and to examine the associations between the discrepancies and psychological and academic outcomes in rural left-behind children and non-left-behind children aged 14–16 in mainland China. Cross-sectional data from a self-report survey were collected in 2020 among 606 rural students (mean age = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…A previous study has reported that rural adolescents appeared to be more vulnerable to symptoms of anxiety and depression compared with urban adolescents in two areas of Zhejiang Province, China [ 28 ]. More than half of the rural participants aged 14–16 in mainland China reported that they felt they were not likely to attain the level of education to which they aspired, and whose aspirations exceed expectations were more likely to report lower self-esteem, higher depression, lower academic self-perception, and poorer self-regulation than those without a discrepancy [ 29 ]. Another reason may be that with the rapid development and urbanization of China in recent years, large numbers of laborers migrated from rural areas to large cities, which has led to the emergence of many left-behind youth in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that rural adolescents appeared to be more vulnerable to symptoms of anxiety and depression compared with urban adolescents in two areas of Zhejiang Province, China [ 28 ]. More than half of the rural participants aged 14–16 in mainland China reported that they felt they were not likely to attain the level of education to which they aspired, and whose aspirations exceed expectations were more likely to report lower self-esteem, higher depression, lower academic self-perception, and poorer self-regulation than those without a discrepancy [ 29 ]. Another reason may be that with the rapid development and urbanization of China in recent years, large numbers of laborers migrated from rural areas to large cities, which has led to the emergence of many left-behind youth in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…40 Chinese children whose aspirations exceed expectations show lower self-esteem and higher rates of depression. 41 Leftbehind children have worse mental health when their parents' educational expectations are higher than children's educational expectations. 42 Some studies deny the impact of educational expectations on adolescent mental health; for example, Reynolds and Baird found that adults who did not meet their early educational expectations did not suffer psychological consequences.…”
Section: Educational Expectations and Adolescent Mental Healthmentioning
confidence: 99%
“… 40 Chinese children whose aspirations exceed expectations show lower self-esteem and higher rates of depression. 41 Left-behind children have worse mental health when their parents’ educational expectations are higher than children’s educational expectations. 42 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the Coleman report, based on the cohort effect in the social interaction theory, extensive studies have explained how school class segregation affects students’ academic achievement and educational attainment, and have argued that school class segregation directly affects students’ educational expectations [ 8 , 20 ]. In the process of interacting with peer groups, students gradually establish their educational expectations, especially those uncertain about their future paths [ 21 , 22 ]. School class composition determines what type of peer group an individual will interact with.…”
Section: Theoretical Foundations and Research Hypothesesmentioning
confidence: 99%